2019
DOI: 10.1186/s13014-019-1341-x
|View full text |Cite
|
Sign up to set email alerts
|

Integrative assessment of brain and bone invasion in meningioma patients

Abstract: Background Various prognostic factors have been suggested in meningioma patients including WHO grading, brain invasion and bone involvement, for instance. Brain invasion was included as an independent criterion in the recent WHO classification. However, assessability of brain or bone involvement is often limited or varies between histopathologic, operative and imaging reports. Objective of our study was to investigate prognostic values including brain and bone involvement according to different cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…the samples (excluding incomplete MRI sequences, brain invasion, etc.) including 1127 cases in the training cohort and 691 cases in the validation cohort were evaluated for brain invasion by the surgeon and imaging records [9] . Surgical records described obvious adhesion between the surface of the tumour and the brain.…”
Section: Methodsmentioning
confidence: 99%
“…the samples (excluding incomplete MRI sequences, brain invasion, etc.) including 1127 cases in the training cohort and 691 cases in the validation cohort were evaluated for brain invasion by the surgeon and imaging records [9] . Surgical records described obvious adhesion between the surface of the tumour and the brain.…”
Section: Methodsmentioning
confidence: 99%
“…To remedy this shortcoming, two recent studies ( 37 , 39 ) sought to ascertain the advantages of a hybrid strategy that contained knowledge from both operative and pathological observations. Their early findings showed that the combined method had the ability to transcend the shortcomings of sole neuropathological evaluation and may be of considerable therapeutic benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Because these high-grade tumors are essentially malignant mesenchymal tumors resembling sarcomas and not true meningiomas, this was somehow expected 18) . Whenever history and radiological findings suggest a grade III meningioma, aggressive excision of bone beyond the nidus and including all abnormal areas on preoperative MRI is warranted 19) .…”
Section: Discussionmentioning
confidence: 99%